2023
DOI: 10.3390/jpm13061009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Survival Benefits of Surgery and Adjuvant Chemotherapy in Neuroendocrine Carcinoma of the Gallbladder: A Population-Based Study with Insight into Future Personalized Therapeutic Approach

Abstract: Background: Neuroendocrine carcinomas of the gallbladder (NECs-GB) are rare tumors, accounting for <0.2% of all neuroendocrine carcinomas of the gastrointestinal tract. They originate from the neuroendocrine cells of the gallbladder epithelium with associated intestinal or gastric metaplasia. The current study is the largest study from the SEER database on NECs-GB that aims to elucidate the demographic, clinical, and pathologic factors influencing the prognosis and comparative survival analysis of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The roles of radiation therapy and chemotherapy were not evident. As with other cancer types, surgical treatment for GB-NENs is widely accepted among researchers, and related studies have demonstrated the importance of surgery in improving survival ( 17 , 46 , 47 ). The significance of postoperative adjuvant chemotherapy in the prognosis of GB-NENs is gradually being confirmed by other relevant research ( 14 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The roles of radiation therapy and chemotherapy were not evident. As with other cancer types, surgical treatment for GB-NENs is widely accepted among researchers, and related studies have demonstrated the importance of surgery in improving survival ( 17 , 46 , 47 ). The significance of postoperative adjuvant chemotherapy in the prognosis of GB-NENs is gradually being confirmed by other relevant research ( 14 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] Surgery by itself was linked to improved short-term (<2 years) result survival, whereas surgery in combination with radiation and adjuvant chemotherapy was related with better long-term (5 years) outcomes. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%